Расчет нормальных допусков с учетом отклонений коэффициентов внешних воздействий - Shilo, G. N.; Kovalenko, D. A.; Gaponenko, N. P. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
The features of forming ellipsoidal tolerance regions under given deviations of external influence coefficients are considered. Methods have been developed for assigning tolerances under the normal distribution law of the main parameters of elements and the coefficients of external factors. The mapping method is used.